2020
DOI: 10.1111/nyas.14520
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hemoglobin levels with age and altitude in preschool‐aged children in Peru: the assessment of two individual‐based national databases

Abstract: According to the World Health Organization, the cutoff hemoglobin (Hb) value for defining anemia is 11 g/dL in preschool‐aged children, and Hb measurements should be corrected above an altitude of 1000 meters. This study sought to determine the altitude at which the Hb value increases compared with that at sea level, Hb changes with age and region in Peru, the prevalence of anemia according to three different models used to correct Hb for altitude, and the association of the Hb value with stunting. Two individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
3
2
0
2
Order By: Relevance
“…A systematic analysis study has shown that the platelet counts of a chronic mountain sickness group were lower compared with the healthy altitude control group [ 45 ]. In addition, the observation that the platelet count is higher in pregnant women at HA than at LA is consistent with the suggestion that populations living in the Southern Andes in Peru are more adapted than those from the central Andes [ 46 ]. These data suggest that adapted people (with higher generational time residing at high altitudes) have, compared to sea level counterparts or non-adapted HA residents, less Hb concentration and higher platelet counts.…”
Section: Discussionsupporting
confidence: 85%
“…A systematic analysis study has shown that the platelet counts of a chronic mountain sickness group were lower compared with the healthy altitude control group [ 45 ]. In addition, the observation that the platelet count is higher in pregnant women at HA than at LA is consistent with the suggestion that populations living in the Southern Andes in Peru are more adapted than those from the central Andes [ 46 ]. These data suggest that adapted people (with higher generational time residing at high altitudes) have, compared to sea level counterparts or non-adapted HA residents, less Hb concentration and higher platelet counts.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, we found that older children exhibited higher Hb levels and a lower prevalence of anaemia, which is following previous findings (40)(41)(42) . The current observation could be partly explained by the significantly lower levels of vitamin A in children aged <10 years, as vitamin A plays a vital role in modulating Fe metabolism and erythropoiesis (43) .…”
Section: Discussionsupporting
confidence: 92%
“…Contrary to our findings, previous studies found no sex-related difference in Hb among young children [38][39][40], but were all in agreement with our findings of higher Hb in older compared to younger age. Unlike those studies which looked at 'healthy' young children in the general population, our children were stunted.…”
Section: Discussionsupporting
confidence: 87%